Antibacterial Effects of Aloe Vera Extracts on some Human and Animal Bacterial Pathogens - Darioush Gharibi; Mohammad Khosravi; Zohreh Hosseini; Fatemeh Boroun; Seyedeh Kolsum Barzgar; Ali Forughi Far (Pasteur Institute of Iran, 2015)
Introduction: Aloe Vera compounds have inhibitory activity on fungi, bacteria, and viruses. This study examines the antibacterial activity of A. Vera purified extracts including gel, boiled skin, boiled gel, and distilled extract against pathogenic bacteria, Staphylococcus aureus, methicillin-resistant S. aureus (MRSA), Klebsiella pneumonia and Pseudomonas aeruginosa were elucidated. Method: The bacterial strains were collected from veterinary hospital. Freshly collected A. vera leaves were used for the juice extraction of gel, skin and distilled extracts. Antibacterial effects of various A. Vera extracts were evaluated using broth microdilution method. The crude polysaccharides of boiled skin extract were purified by phenol method; and fractionated by anion exchange chromatography. For each bacterium, minimum inhibitory concentration of various A. Vera extracts was determined. The protein expression changes of treated bacteria were detected by SDS-PAGE electrophoresis. Results: The distillate extract exhibited more antibacterial effects than other extracts. Out of seven-carbohydrate fractions of the skin extract, the fractions 6 and 7 had antibacterial effects on S. aureus and MRSA at 0.089 and 0.134 mg/ml, respectively; also fraction 5 showed antibacterial effects on MRSA at 0.113 mg/ml concentration. The protein profiles of these strains before and after treatment with A. Vera showed significant differences at 175, 60, 200 and 70 kDa protein bands of S. aureus, MRSA, P. aeruginosa and K. pneumonia, respectively. Conclusion: This finding showed that the distillate extract despite the minimal amount of carbohydrate and protein was more efficient against both Gram-positive and Gram negative bacteria.